PENERAPAN PENDEKATAN SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALLY DENGAN MEDIA ALAT BANTU HITUNG SEDERHANA UNTUK MENINGKATKAN PEMBELAJARAN BILANGAN BULAT BAGI SISWA KELAS IV SDN 7 KEBUMEN TAHUN AJARAN 2015/2016. - ANDREANTO, FINDI JULI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Findi Juli Andreanto. The Application of Somatic, Auditory, Visualization, Intellectually Approach Using Simple Counting Tools to Improve Learning about Integers for the Fourth Grade Students of SD Negeri 7 Kebumen in the Academic Year of 2015/2016. The objectives of this research are to improve Mathematics learning for the fourth grade students of SDN 7 Kebumen. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings. Subjects of the research were 18 students of the fourth grade of SD Negeri 7 Kebumen. Techniques of collecting data were test and non-test.This research is finished after the learning process and learning outcomes of students reached minimum completeness criteria of 70 by 80%. The results of this research showed that the application of SAVI approach using simple counting tools can improve Mathematics learning about integers for the fourth grade students of SD Negeri 7 Kebumen in the academic year of 2015/2016.Keywords: SAVI, simple counting tools, learning, Mathematics Abstrak: Findi Juli Andreanto. Penerapan Pendekatan Somatic, Auditory, Visualization, Intellectually dengan Media Alat Bantu Hitung Sederhana untuk Meningkatkan Pembelajaran Bilangan Bulat Bagi Siswa Kelas IV SDN 7 Kebumen Tahun Ajaran 2015/2016.Tujuan penelitian ini adalah untuk meningkatkan pembelajaran Matematika pada siswa kelas IV SDN 7 Kebumen. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 3 siklus. Setiap siklus terdiri dari dua pertemuan. Subjek penelitian ini adalah siswa kelas IV SDN 7 Kebumen yang berjumlah 18 siswa.Teknik pengumpulan data berupa teknik tes dan nontes. Penelitian dihentikan setelah hasil pembelajaran siswa mencapai KKM = 70 sebanyak 80% siswa. Hasil penelitian menunjukkan bahwa penerapan pendekatan somatic, auditory, visualization, intellectually dengan media alat bantu hitung sederhana dapat meningkatkan pembelajaran Matematika materi bilangan bulat bagi siswa kelas IV SDN 7 Kebumen tahun ajaran 2015/2016.Kata Kunci: Somatic, auditory, visualization, intellectually, media alat bantu hitung sederhana, pembelajaran, Matematika, bilangan bulat